Synopsis of the pinhole borers of West Malaysia (Coleoptera: Curculionidae: Platypodinae) - Beaver, Roger A.; Smith, Sarah M.; Ong, Su Ping; Cognato, Anthony I. (Zootaxa, 2026)
A synopsis of the West (Peninsular) Malaysian fauna of platypodine pinhole borer beetles is provided with information on local and world distribution, host trees, biology and taxonomy. One hundred and thirty-eight species are recorded from West Malaysia, eight for the first time. Diapus borneensis Browne comb. res. and Diapus pendleburyi Schedl comb. res. are restored to Diapus Chapuis from Genyocerus Motschulsky. Platypus philippinensis (Schedl) comb. res. is restored to Platypus Herbst from Dendroplatypus Browne. Attention is drawn to the presence of wax glands on the elytra as a possible synapomorphy defining the genus Genyocerus, and to the probable polyphyly of Peroplatypus Wood and Treptoplatypus Schedl. We also list 16 species for which ‘Malaya’ is included in the distribution in various catalogues, but for which we have been unable to find published records or see West Malaysian specimens. These records require confirmation.